Control of DC Bus Voltage in a 10 kV Off-Grid Wind–Solar–Hydrogen Energy Storage System - Jiangzhou Cheng; Jialin Meng; Gang Bao; Xinyu Hu (Energies)
We propose a coordinated control strategy for off-grid 10 kV wind–solar–hydrogen energy storage DC microgrid systems based on hybrid energy storage and controllable loads to improve their stability and accommodation level. First, mathematical models of each unit are established based on the operating characteristics of wind turbines, photovoltaic (PV) units, alkaline electrolyzers, fuel cells, and lithium batteries. Second, on the side of the electro-hydrogen hybrid energy storage DC/DC converter, the traditional dual-loop control is improved by proposing a control scheme combining an extended state observer with adaptive backstepping control (ESO-adaptive backstepping). On the load demand side, an electric spring incorporating adaptive fuzzy control (AFC) is introduced to adjust and compensate for the voltage. Finally, an actual case analysis is conducted using data from the Ningbo Cixi hydrogen–electric coupling DC microgrid demonstration project. The results demonstrate that the control method proposed in this study significantly outperforms the traditional double closed-loop control method. Specifically, the proposed method reduces the bus voltage fluctuation range in the presence of load disturbances by 24.07% and decreases the stabilization time by 56.92%. Additionally, the efficiency of the hydrogen fuel cell is enhanced by 31.88%. This control method can be applied to 10 kV DC microgrid systems with distributed energy resources. It aims to reduce the fluctuation amplitude of the DC bus voltage and enhance the system’s ability to withstand transient impact events.